2019
DOI: 10.3389/fimmu.2019.00724
|View full text |Cite
|
Sign up to set email alerts
|

The F1F3 Recombinant Chimera of Leishmania donovani-Nucleoside Hydrolase (NH36) and Its Epitopes Induce Cross-Protection Against Leishmania (V.) braziliensis Infection in Mice

Abstract: Leishmania ( V .) braziliensis is the etiological agent of Cutaneous (CL) and Mucocutaneous leishmaniasis (ML) in the New World. CL can be more benign but ML can be severe and disfiguring. Immunity to these diseases include hypersensitivity, an enhanced inflammatory response with strong IFN-γ and TNF-α secretion. Additionally, the production of IL-10 which down modulates the immune response is reduced. The Nucleoside hydrolase (NH36) of Leish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
(127 reference statements)
0
9
0
Order By: Relevance
“…Currently, there is not any approved vaccine against human leishmaniasis. 5 Nevertheless, several vaccine formulations are under evaluation in preclinical 6 , 7 , 8 and clinical trials (ClinicalTrials.gov Identifier: NCT02894008 and NCT03969134). The need to induce a Th1-type immune response in order to obtain protection was shown in Leishmania -murine models protection studies and in the immune profiles of self-healed individuals.…”
mentioning
confidence: 99%
“…Currently, there is not any approved vaccine against human leishmaniasis. 5 Nevertheless, several vaccine formulations are under evaluation in preclinical 6 , 7 , 8 and clinical trials (ClinicalTrials.gov Identifier: NCT02894008 and NCT03969134). The need to induce a Th1-type immune response in order to obtain protection was shown in Leishmania -murine models protection studies and in the immune profiles of self-healed individuals.…”
mentioning
confidence: 99%
“…Furthermore, we noticed that most of the peptide pools containing both HLA-I and -II epitopes induced higher amounts of IFN-γ than those containing only HLA-I or -II epitopes. These results emphasize the importance to include both CD4 + and CD8+ specific T cell epitopes in peptide based vaccines [67,88,89].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 72%
“…However, as we have described here, Agallou and colleagues designed multi-epitope peptides containing both MHC-I and -II restricted epitopes that were able to induce both IFN-γ-producing CD4+ and CD8+ T cells in immunized mice [40]. More interestingly, it was recently reported that mice vaccination with a chimera vaccine composed of F1 and F3 NH36 domains, holding respectively, epitopes involved in both CD8+ and CD4+ T cell mediated protective responses, was more efficient than vaccination with either of the domains injected separately [67,89].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly conserved immunogenic proteins or epitopes between Leishmania spp. have the potential to confer cross-protection as demonstrated for L. donovani nucleoside hydrolase (NH36) and/or its recombinant fragments F1 (N-terminal domain) and F3 (C-terminal domain) formulated with saponin, which induced antigen-specific protection in BALB/c mice against L. amazonensis and L. braziliensis [157][158][159]. Other Leishmania proteins evaluated as vaccine candidates are reviewed in [160].…”
Section: Vaccines For Leishmaniasismentioning
confidence: 99%